Natural Language Processing and Information Systems : 25th International Conference on Applications of Natural Language to Information Systems, NLDB 2020, Saarbrücken, Germany, June 24-26, 2020, Proceedings /: 25th International Conference on Applications of Natural Language to Information Systems, NLDB 2020, Saarbrücken, Germany, June 24-26, 2020, Proceedings. (2020) - Unknown
No abstract available